Antimicrobial susceptibility profiles of multidrug-resistant aeromonads isolated from Northern Portugal freshwater ecosystem. - Varandas, Simone (2022)
Extensive use of water and anthropogenic activities contribute to water body pollution. Agricultural, urban, and animal waste, often characterized by numerous toxic and carcinogenic chemicals, pathogenic bacteria, and antibiotics, as well as antibiotic resistance genes (ARGs), loaded with microflora, can contaminate water and enter the food chain, posing a considerable danger to public health [1,2]. The inappropriate use of antibiotics, one of the causes of the high incidence of antimicrobial-resistant bacteria isolated from aquatic ecosystems, represents a risk for aquatic organisms and the welfare of humans. Infectious diseases, both human and animal, are closely related through the environment in the One World - One Medicine - One Health concept, in order to deal with the growing problem of antibiotic resistance. Aeromonas spp. can acquire antimicrobial resistance mechanisms, with the potential to spread via horizontal gene transfer, so they could be a good candidate as an indicator to follow antimicrobial resistance dissemination in water [3,4]. This study aimed to determine the antimicrobial resistance rates among riverine Aeromonas spp., taken as representative of the autochthonous microbiota, to evaluate the level of antibacterial resistance in the Tua River (Douro basin).